Defining the Hallmarks of Metastasis - Welch, Danny R.; Hurst, Douglas R. (Cancer research (Chicago, Ill.), 2019)
Metastasis is the primary cause of cancer morbidity and mortality. The process involves a complex interplay between intrinsic tumor cell properties as well as interactions between cancer cells and multiple microenvironments. The outcome is the development of a nearby or distant discontiguous secondary mass. To successfully disseminate, metastatic cells acquire properties in addition to those necessary to become neoplastic. Heterogeneity in mechanisms involved, routes of dissemination, redundancy of molecular pathways that can be utilized, and the ability to piggyback on the actions of surrounding stromal cells makes defining the hallmarks of metastasis extraordinarily challenging. Nonetheless, this review identifies four distinguishing features that are required: motility and invasion, ability to modulate the secondary site or local microenvironments, plasticity, and ability to colonize secondary tissues. By defining these first principles of metastasis, we provide the means for focusing efforts on the aspects of metastasis that will improve patient outcomes.